1985
DOI: 10.1073/pnas.82.7.2111
|View full text |Cite
|
Sign up to set email alerts
|

Common haplotype dependency of high G gamma-globin gene expression and high Hb F levels in beta-thalassemia and sickle cell anemia patients.

Abstract: We have studied 42 homozygous 3-thalassemia patients from Algeria and 34 sickle cell anemia patients from Senegal and Benin, determinin* the relationship between haplotypes, Hb F, and G7yglobin/ -globin ratios. Populations selected have a high frequency of haplotype homozygotes because of consanguinity (Algeria) and geographic homogeneity (West Africa). We find in (-thalassemia In addition, haplotypes IX, m, and Senegalese sickle cell anemia patients exhibit hematological amelioration of their disease. Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0
12

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(134 citation statements)
references
References 9 publications
5
117
0
12
Order By: Relevance
“…Conversely, the XmnI+ is a common polymorphism that has been extensively explored in different populations and has been shown to influence the number of FC and HbF levels in normal 30,31 and anaemic subjects. 20,21 The (AT) 9 T 5 configuration (configuration W), which is located within a putative transcriptional silencer 32 of the b globin gene, was originally described in a silent b thalassaemia case 33 and has been shown to be associated with reduced sickle gene expression. 34 However, another study involving a few non-anaemic subjects, did not confirm this effect on b globin gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the XmnI+ is a common polymorphism that has been extensively explored in different populations and has been shown to influence the number of FC and HbF levels in normal 30,31 and anaemic subjects. 20,21 The (AT) 9 T 5 configuration (configuration W), which is located within a putative transcriptional silencer 32 of the b globin gene, was originally described in a silent b thalassaemia case 33 and has been shown to be associated with reduced sickle gene expression. 34 However, another study involving a few non-anaemic subjects, did not confirm this effect on b globin gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Some studies have suggested that this cluster is involved in the variability of HbF expression and FC number in individuals with one (heterozygote) or two copies of the b thalassaemic (b thal) or the sickle cell gene, whereas others failed to confirm these findings. 12,13 Studies of sequence variations in the Locus Control Region hypersensitive site-2 (b LCR 5'HS2), 14 ± 16 the second intron of the A g gene (Ag IVS2), 17 the promoter region of the b globin gene 18,19 and the -158 5' of the Gg gene 20,21 have found a genetic association with HbF levels, FC number or both. These association studies have so far been performed exclusively on populations subjected to different degrees of anaemic stress or on carriers of various b globin gene defects.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] The regulation of HbF level might be a complex genetic trait governed by genetic elements linked to the b-globin gene-like cluster and quantitative trait loci (QTL) present on chromosomes 6, 8 and on the X-chromosome; other regulatory loci are also likely to exist and epigenetic and cellular factors could also have regulatory roles. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] It is possible that these and other regulatory elements also modulate the HbF response to HU. Accordingly, we hypothesized that single nucleotide polymorphisms (SNPs) in candidate genes or QTL with putative roles in the regulation of HbF production might modulate the HbF response to treatment with HU.…”
Section: Introductionmentioning
confidence: 99%
“…Un taux résiduel élevé d'hémoglobine foetale (HbF) est un facteur atténuateur. En décortiquant les marqueurs géné-tiques issus de l'étude, Dominique Labie identifie un polymorphisme en amont d'un des gènes de globine foetale comme étant spécifiquement lié à la variabilité du taux d'HbF [2]. De façon réconfortante, en 2008, le groupe de Stuart Orkin à Boston, par les approches actuelles dites « tout génome », identifie trois locus, dont le polymorphisme explique 50 % de la variabilité du taux d'HbF.…”
Section: Référencesunclassified